The role of endogenous antioxidants in scald development of 'Beurré D'Anjou' pears under different storage systems - Calvo, Gabriela; Candan, Ana Paula; Recasens Guinjuan, Inmaculada; Larrigaudière, Christian (ISHS, 2025)
Trabajo presentado al VIII International Postharvest Symposium: Enhancing Supply Chain and Consumer Benefits - Ethical and Technological Issues. Cartagena, Murcia (España), junio 2016